Pengaruh harga, kualitas pelayanan, dan citra merek terhadap kepuasan pelanggan pada pengguna Po Rosalia Indah - Utomo, Fahman Hadi; Rizkiawan, Ilham Karin; Khasanah, Aulia Uswatun; Nuralamsyah, Dicky (Journal of Management and Digital Business, 2024)
Customer satisfaction is a feeling of pleasure or disappointment from a buyer after purchasing goods or services and making an assessment and comparison of the results and also their expectations. Several factors influence customer satisfaction: price, service quality, and brand image. This study aimed to test whether price, service quality, and brand image positively affect PO Rosalia Indah's customer satisfaction in the Special Region of Yogyakarta. This study used purposive sampling to determine the sample and a questionnaire to collect data distributed to 176 respondents who are users of Po Rosalia Indah in the Special Region of Yogyakarta. This study used multiple linear regression data analysis. The results of the study showed that price had a positive effect on customer satisfaction. Service quality had a positive effect on customer satisfaction; brand image had a positive effect on customer satisfaction. The results of the simultaneous test of price, service quality, and brand image had a simultaneous effect on customer satisfaction of users of Po Rosalia Indah in the Special Region of Yogyakarta.